Translation Studies: Theory and Practice - Byalyk, V.D., Mykytiuk I. M. (Chernivtsi Chernivtsi National University, 2012)
This book is greared towards students and teachers of translation. It may also be of use to anybody who is not indifferent to translation studies. This bookwill help students to acknowledge the circle of issues associated with translation as a peculiar type of human activity.
Keywords: Literature